A dual-amplified ROS-responsive nanosystem with self-accelerating drug release for synergistic chemotherapy. Issue 21 (22nd February 2023) - Li, Jun; Zong, Qingyu; Zhao, Zhongyi; Yuan, Youyong
Abstract : Herein, we have developed a ROS-responsive nanosystem (PTCD@B) equipped with a dual-cycle amplification effect to improve the prodrug activation efficiency and tumor selectivity for synergistic chemotherapy. Abstract : In this work, we have developed a tumor-specific self-accelerating prodrug activation nanosystem consisting of self-amplifying degradable polyprodrug PEG-TA-CA-DOX and encapsulated fluorescent prodrug BCyNH2, equipped with a reactive oxygen species dual-cycle amplification effect. Furthermore, activated CyNH2 is a therapeutic agent with potential to synergistically improve chemotherapy.